Synergistic effects of fluoride and chloride on general corrosion behavior of AISI 316 stainless steel and pure titanium in H2SO4 solutions. (January 2018) - Wang, Z.B.; Hu, H.X.; Zheng, Y.G.
Highlights: F − and Cl − can accelerate the corrosion of 316 stainless steel in H2 SO4 solutions. The effects of Cl − on the corrosion of pure titanium depend on the F − content. Different synergistic effects of F − and Cl − on corrosion of two materials are found. Interaction effects of F − and Cl − on their ingress into the film are assessed by XPS. The general corrosion rates are compared for two materials under present conditions. Abstract: The general corrosion behavior of AISI 316 stainless steel (316 SS) and pure titanium (pure Ti) in H2 SO4 solutions containing fluoride (F − ) and chloride (Cl − ) ions was evaluated quantitatively using potentiodynamic polarization tests. The general corrosion resistance of these two materials to F − and Cl − is compared and explained by the proposed mechanisms based on XPS analyses. Furthermore, F − and Cl − are found to have synergistic effects on the general corrosion behavior of these two materials, which are attributed to the effects of F − and Cl − on the penetration of each other into the film.